Effects of competitive standard, team formation and playing position on match running performance of Brazilian professional soccer players - Aquino, R.; Palucci Vieira, L. H.; Carling, C.; Martins, G. H. M.; Alves, I. S.; Puggina, E. F. (International Journal of Performance Analysis in Sport, 2017)
This study examined the effects of competitive standard, team formation and playing position on match running performance in a Brazilian professional soccer team. Performance was investigated in 36 players in 48 matches at 3 competitive standards: 1st São Paulo State Championship; 3rd and 4th Brazilian leagues. Global Positioning System technology was used to determine total distance covered (TD), maximal running speed (MRS), mean speed (SMEAN) and frequency of high-intensity activities (HIA). Data were compared across competitive standards, team formations and playing positions. Magnitude-based inferences showed greater values for TD, SMEAN and HIA (likely to almost certain) in the lower national (3rd, 4th Brazilian) vs. the top state division (1st São Paulo). Higher values for all variables were reported for the 1-4-3-3 vs. the 1-4-4-2 formation (likely to almost certain). External defenders/midfielders and forwards reported greater values (likely to almost certain) vs. central defenders/midfielders, especially in HIA. Linear regression analyses showed that playing position demonstrated a higher relative contribution to the variance in MRS (24%) and HIA (29%) compared to team formation (16 and 25%, respectively). In a Brazilian professional soccer team, match running performance was dependent upon competitive standard, playing formation and playing position.